A comparison of the pharmacokinetics and safety of enzalutamide in subjects with hepatic impairment and matched healthy subjects. (1st March 2017) - Krauwinkel, W.; Noukens, J.; van Dijk, J.; Popa, S.; Ouatas, T.; de Vries, M.; Phung, D.; Gibbons, J.; Mordenti, J.; Mateva, L.
Summary: What is known and objective: Enzalutamide is an androgen receptor inhibitor approved for treatment of metastatic castration‐resistant prostate cancer. Enzalutamide is highly protein bound and eliminated primarily by hepatic metabolism; therefore, it is important to understand whether enzalutamide pharmacokinetics is altered by hepatic impairment. Methods: Pharmacokinetic data were obtained from two non‐randomized, open‐label, single‐dose, phase 1 studies conducted in patients with mild (Child‐Pugh class A, n = 6) or moderate (Child‐Pugh class B, n = 8) hepatic impairment (NCT01901133) or severe (Child‐Pugh class C, n = 8) hepatic impairment (NCT02138162) and their corresponding matched healthy controls; data from both studies are presented here. Subjects with hepatic impairment had liver cirrhosis ( n = 19) or chronic hepatitis ( n = 3). All subjects received a single oral dose of 160 mg enzalutamide under fasting conditions, with blood samples collected predose and up to 49 days post‐dose. Results and discussion: Exposure to enzalutamide active moieties, based on the area under the curve of the sum of enzalutamide and N ‐ desmethyl enzalutamide (an active metabolite with similar potency to enzalutamide), increased by 13%, 18% and 4% in subjects with mild, moderate and severe hepatic impairment, respectively, relative to matched controls. Compared with healthy controls, the mean maximum plasma concentration for enzalutamide active moieties was 24% higher in subjects with mild hepatic impairment and 11% and 41% lower in subjects with moderate and severe hepatic impairment, respectively. Enzalutamide was generally well tolerated, with no clinically significant trends in abnormal laboratory findings, vital signs or electrocardiograms. What is new and conclusions: No major differences in single‐dose pharmacokinetics were observed in subjects with hepatic impairment vs. matched healthy controls. Therefore, these studies indicate that no initial dose adjustment is necessary when administering enzalutamide to patients with hepatic impairment. Abstract : Enzalutamide, an androgen receptor inhibitor approved for the treatment of metastatic castration‐resistant prostate cancer, is eliminated primarily by hepatic metabolism. In this analysis, mild to severe hepatic impairment did not have a clinically meaningful effect on the pharmacokinetics and safety of enzalutamide active moieties compared with matched healthy controls. Thus, no initial dose adjustment is necessary when administering enzalutamide to patients with mild to severe hepatic impairment.